(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Uzbekistan is undergoing significant reforms aimed at fostering economic stability and social inclusion. This study evaluates the effectiveness of fiscal, monetary, and social policies using econometric modeling and statistical analyses. By integrating quantitative findings with qualitative insights, we explore the implications of targeted interventions on poverty reduction, income distribution, and economic resilience. The results demonstrate the interconnectedness of macroeconomic policies and social equity, providing actionable recommendations for sustainable development.